Hyperinsulinemic Hypoglycemia Secondary to Multiple β Cell Adenomas in a Boxer Bitch - Barajas López, Ignacio Netzahualcoyotl (2019)
Background: The most frequent pancreatic tumours are derived from insulin-secreting β cells, commonly called in-sulinomas; these are characterised by high insulin secretion causing hypoglycemia and clinical signs such as seizures, tremors, weakness, and polyphagia, among others. In dogs, this tumour represents <0.5% of neoplasias; the majority are solitary carcinoma masses and rarely adenomas. Insulin-secreting tumours are usually diagnosed in middle-aged or older dogs. There is no apparent sex predilection for the disease and it has been mainly reported in medium to large breeds. Independently of whether they are adenomas or carcinomas, dogs have the same disease-free time and survival time and the prognosis is poor. Case: An 8-year-old female Boxer was brought to the University Veterinary Hospital with a history of weakness, tremors, and generalised convulsions. Physical examination, CBC and urinalysis revealed no abnormalities. In the blood chemistry profile, hypoglycemia was detected along with hyperinsulinemia. An abdominal ultrasound revealed the presence of two abnormal masses located in the pancreas. The insulin:glucose ratio was 59.8. Exploratory celiotomy was performed and two masses were located in the mesentery, adjacent to the left pancreatic lobe, and a third was in the pancreatic tissue of the same lobule. All masses were resected during the same surgery. Cytology of the masses coincided with apparently malignant insulinoma, however, the histopathological and immunohistochemically report indicated an insulin-secreting adenoma. The patient improved clinically and remained stable for approximately 545 days, after which seizures relapsed and a new treatment was not approved. The patient died 575 days after surgery. Discussion: In dogs, pancreatic islet cell tumours correspond to endocrinologically active neoplasm that secrete hormones and are associated with functional disorders (hyperinsulinemia) in relation to hypoglycemia. Hypoglycemia causes episodic signs that are generally observed for a few seconds to several minutes, because of regulatory compensatory mechanisms. In animals, rapid hypoglycaemia activates the sympathetic nervous system via hypothalamic glucoreceptors, producing signs such as tachycardia, tremors, nervousness, irritability, and intense hunger. Other clinical signs are related to neuro-glycopenia by a decrease in blood glucose, which stimulates the autonomic nervous system, causing hypothermia, lethargy, weakness, ataxia, collapse, muscular fasciculation, convulsions, and coma. The diagnosis of an insulin-secreting tumour requires confirmation of hypoglycemia with evidence of elevated insulin secretion and the identification of a pancreatic mass by ultrasonography or exploratory celiotomy. An insulin:glucose ratio >30 is indicative of insulinoma. Unfortu-nately, the specificity of the amended insulin:glucose ratio is poor. In the past, there has been confusion with respect to their biological nature, because, based on histological and electron microscopic evaluations, 60% of these neoplasms are carcinomas and 40% are adenomas. Nevertheless, these claims were not substantiated and most insulinomas are currently considered to be malignant (carcinomas). The objective of this paper was to present a rare case of a Boxer dog that had three β cell tumours of the pancreas, which produced hyperinsulinemia and hypoglycemia. Although this is not a malignant tumour, we demonstrated, as described in the literature, that regardless of the histopathological classification, insulin-producing tumours have a poor prognosis in dogs.